2013
DOI: 10.1021/ja4066943
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the α-Effect in Gas-Phase SN2 Reactions of Microsolvated Anions

Abstract: The α-effect-enhanced reactivity of nucleophiles with a lone-pair adjacent to the attacking center-was recently demonstrated for gas-phase S(N)2 reactions of HOO(-), supporting an intrinsic component of the α-effect. In the present work we explore the gas-phase reactivity of microsolvated nucleophiles in order to investigate in detail how the α-effect is influenced by solvent. We compare the gas-phase reactivity of the microsolvated α-nucleophile HOO(-)(H2O) to that of microsolvated normal alkoxy nucleophiles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 51 publications
4
74
1
Order By: Relevance
“…The latter then breaks down to give the products complex (Pro‐COM) CH 3 Nu(H 2 O) n ⋯Cl − . Subsequently, the Pro‐COM dissociates into CH 3 Nu and Cl − (H 2 O) n through a low‐barrier water‐migration TS, [CH 3 Nu⋯(H 2 O) n ⋯Cl] − ≠ , that is the more exothermic reaction channel . The energetics of reactants complex, inversion TS, products complex, and final products relative to separated reactants are listed in Table S1 (see Supporting Information).…”
Section: Resultssupporting
confidence: 85%
“…The latter then breaks down to give the products complex (Pro‐COM) CH 3 Nu(H 2 O) n ⋯Cl − . Subsequently, the Pro‐COM dissociates into CH 3 Nu and Cl − (H 2 O) n through a low‐barrier water‐migration TS, [CH 3 Nu⋯(H 2 O) n ⋯Cl] − ≠ , that is the more exothermic reaction channel . The energetics of reactants complex, inversion TS, products complex, and final products relative to separated reactants are listed in Table S1 (see Supporting Information).…”
Section: Resultssupporting
confidence: 85%
“…However, the reaction rate constant measured for F À (CH 3 OH) 2 + C 2 H 5 Br was larger than the reaction rate constant measured for F À (CH 3 OH) + C 2 H 5 Br at both 200 and 250 K. Interestingly, the decrease in efficiency with increasing solvation was also somewhat muted for the reactions with C 2 H 5 Br, though the reasons behind these observations are unknown. Table 1 Reaction rate constants, reaction efficiencies, product ion branching ratios (BR), and exothermicities for S N 2 and E2 pathways for each reaction at 300 K. Reaction k (10 À10 cm 3 molec À1 s À1 ) at 300 K Reaction efficiency (k/k col ) Ionic product BR at 300 K DH rxn S N 2 (kJ mol À1 ) DH rxn E2 (kJ mol À1 ) F À + CH 3 …”
Section: Resultsmentioning
confidence: 99%
“…The addition of a small number of solvent molecules to gas-phase ions provides insight into this transition. Recent investigations of microsolvated ions have addressed the impact of solvation on mechanisms [2], reactivity [3], reaction dynamics [4][5][6][7][8], vibrational energy transfer [9,10], and delocalization of charge [11].…”
Section: Introductionmentioning
confidence: 99%
“…A few years later, however, the same laboratory arrived at the opposite conclusion and obtained experimental validation of the α ‐effect in the gas‐phase from a thorough thermochemical analysis . The influence of solvation was then reinvestigated Bierbaum and co‐workers, through the investigation of the gas‐phase reactivity of monosolvated nucleophiles. It was found that coordination of a single water molecule to the nucleophile resulted in a smaller PA and higher barrier compared to unsolvated nucleophiles.…”
Section: Variation Of Nucleophile and Leaving Groupmentioning
confidence: 99%